PENGUATAN KETAHANAN KELUARGA MELALUI SOSIALISASI NILAI-NILAI TASAWUF DALAM KELUARGA MUSLIM - Lintang Seira Putri; Mamluatur Rahmah; Eri Erdetya (AL HAZIQ: Journal of Community Service, 2025)
The family is the first environment for individuals to shape their character, values, and behavior. However, modern challenges such as shifting cultural values, the influence of social media, and increasing family conflicts require strong family resilience. This activity aims to educate the community about efforts to strengthen Muslim family resilience through the dissemination of Sufi values. The community service activity was carried out at the Nur Hasanah Mosque study group in Kampung Baron Cilik, Laweyan, Surakarta, through several stages, namely an initial survey, material preparation, implementation of two educational sessions, and evaluation. The material presented included the concept of a resilient family and the implementation of Sufi values such as patience, gratitude, trust in God, and spiritual awareness in family life. The evaluation was conducted using pretest and posttest questionnaires for 35 participants. The results showed that 30 participants (85.7%) experienced an increase in their understanding of family resilience and Sufi values, while 5 participants (14.3%) did not show any improvement. These findings indicate that strengthening Sufi values contributes positively to improving the understanding and readiness of Muslim families to face challenges and crises adaptively.